Determinants of corporate sustainability message sharing on social media: A configuration approach - Knight, Hanne (2021)
With an increasing number of consumers receiving information on social media, companies have adopted these channels to communicate their sustainability efforts. Digital channels enable reaching large audiences in a short period of time, and engaging consumers in message sharing activities to reap those rewards has its own challenges. Companies need to understand what increases sharing of their sustain ability messages, but they must be mindful of not overstating their sustainability efforts which may be perceived as greenwashing. The Information Adoption Model is used to assess how message information quality and source credibility affect sharing of corporate sustainability messages. A fuzzy-set Qualitative Comparative Analysis is conducted on a survey of UK social media users (n = 527). Results show that dimensions of information quality and source credibility act in combination to influ ence sustainability message sharing. The study informs managers what to stress in social media message planning to facilitate effective sustainability communications.